Discordance between fat mass index and body mass index is associated with reduced bone mineral density in women but not in men: the Busselton Healthy Ageing Study. Issue 1 (January 2017) - Zhu, K.; Hunter, M.; James, A.; Lim, E.; Cooke, B.; Walsh, J.
Abstract Summary The obesity-BMD relationship is complex. In 3045 middle-aged adults, we found that in women (but not men) with discordant fat mass index (FMI)/BMI categories, higher body fat for BMI was associated with lower BMD, suggesting that increased fat mass without an accompanying increase in lean mass may be deleterious to bone. Introduction The relationship between obesity and BMD is complex. FMI (fat mass (kg) / height (m)2 ) is a more accurate measure of fatness than BMI, and depending on body composition, some individuals have discordant BMI/FMI categories. We examined associations between FMI, BMI and BMD in participants in the Busselton Healthy Ageing Study. Methods Body composition and BMD of the hip, spine and total body were measured using DXA in 3045 participants (1644 females) aged 45–67 years. Using standard BMI/FMI categories, the participants were classified as underweight/fat deficit, normal, overweight/excess fat, obese I and obese II–III. Results BMI and FMI categories were concordant in 77.3 % of females and 71.2 % of males. There were 12.9 % females and 13.2 % males in a higher FMI than BMI category (high body fat for BMI), whereas 9.8 % females and 15.6 % males were in a lower category (low body fat for BMI). Females with high body fat for BMI had significantly lower covariate-adjusted BMD at the femoral neck, total hip and total body (differences of 3.8, 5.1 and 2.6 %, respectively, allP < 0.05) than females with low body fat for BMI and lower total body BMD than women with concordant FMI/BMI (by 1.4 %, P = 0.04). In males, BMD did not differ significantly between those who were concordant or discordant for FMI/BMI categories. Conclusion In women (but not men) with discordant FMI/BMI categories, higher body fat for BMI was associated with lower BMD, suggesting that increased fat mass without an accompanying increase in lean mass may be deleterious to bone.